2019
DOI: 10.1021/acs.cgd.9b00312
|View full text |Cite
|
Sign up to set email alerts
|

Organic Polymers of an Angular Diene via Solid State [2 + 2] Polymerization: Coordination Polymers with Dicarboxylates as Templates

Abstract: A new class of organic polymers have been synthesized via solid-state [2 + 2] photopolymerization reaction of coordination polymers (CPs) of an angular diene, namely, 3,3′-(1,3-phenylene)bis(N-(3-pyridyl)acrylamide) (L), with dicarboxylates as ancillary ligands. Five CPs of L have been studied, which includes three types of dicarboxylates and five metal ions such as Co(II), Cu(II), Cd(II), Ni(II), and Zn(II). Two of the three dicarboxylates contain angular (isophthalate/glutarate) geometry and one contains lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…The salts (HCOOH, HCl/H 2 SO 4 ) of these 1D‐polymers have shown an excellent ability to form flexible plastic films. We have further explored such photochemical polymerizations in the coordination polymers of dienes, which produced crystalline coordination polymers of organic polymers (CPOPs) . In continuation of our efforts in this direction, two new dienes containing 1,4‐diaryl bis amide as spacers and 3‐picolyl ( 1 ) and 4‐picolyl ( 2 ) moieties as end groups (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The salts (HCOOH, HCl/H 2 SO 4 ) of these 1D‐polymers have shown an excellent ability to form flexible plastic films. We have further explored such photochemical polymerizations in the coordination polymers of dienes, which produced crystalline coordination polymers of organic polymers (CPOPs) . In continuation of our efforts in this direction, two new dienes containing 1,4‐diaryl bis amide as spacers and 3‐picolyl ( 1 ) and 4‐picolyl ( 2 ) moieties as end groups (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…We have further exploreds uch photochemical polymerizations in the coordination polymers of dienes, which produced crystalline coordination polymers of organic polymers (CPOPs). [26,27] In continuation of our efforts in this direction, two new dienes containing 1,4-diaryl bis amide as spacers and 3-picolyl (1)a nd 4-picolyl (2)m oieties as end groups (Scheme 1). Although both these molecules have as imilar backbone, they are expected to form different crystal structures as the 4-pyridyl derivatives of this class of molecules have at endency to form hydrates and ex-hibit unpredictable hydrogen bonding patterns,w hile the 3pyridyl derivatives form b-sheet networks that make the single crystalsp hotostable.…”
mentioning
confidence: 99%
“…CPs can supply stereo-directive templating through olefin pre-arrangement; however, the preorganization of multiple CC pairs is challenging to manage at the molecular level because of the dynamic nature of CC bonds . Previous works showed that cyclobutane isomers with specific configurations can be derived from corresponding CP precursors, , by manipulation of metal ions and auxiliary ligands, the presence of guest molecules, , the photoirradiation wavelengths, , gas pressures, mechanical force, or temperature . To boost a synthetic strategy for the interconversion of cycloisomers would potentially enable the rational synthesis of multi-cyclic compounds starting from a single precursor (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…As is known, the photocatalytic effect of MOFs strongly depends on the central metals and the conjugation degree of organic ligands. Organic ligands also influence the self-assembly of porous MOFs, endowing MOFs the diversity in shape and size of pores. The abundant catalytic sites and specific surface areas make MOFs possess outstanding catalytic activities. Some MOFs containing 4,4′,4″-nitrilotribenzoic acid (H 3 NTB) ligands were usually reported to have photocatalytic activity. For example, Lan’s group synthesized a series of MOFs utilizing H 3 NTB ligands, which showed highly photocatalytic activities for the CO 2 reduction reaction. , Su’s group obtained a 3D Co-MOF with a twofold interpenetrating structure by using H 3 NTB ligands, which acted as a heterogeneous catalyst to degrade RhB in water through activating peroxymonosulfate (PMS) to generate sulfate radicals .…”
Section: Introductionmentioning
confidence: 99%